Polychronic-polygenic spatial-paragenetic ilmenite bearing of the Bukinska area of the Mezhyrichny deposit of titanium ores - Figura, Lubov; Kovalchuk, Myron (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Introduction. The primary task, aimed at meeting the needs of our own titanium raw materials, is to put into operation as soon as possible the deposits in which spatially and paragenetically different ore bearing capacity is combined in a spatial and paragenetic way and which have sufficient detail been studied. One of these deposits is Mezhyrichne, which is located within the Volyn megablock, in the central part of the Korosten pluton, Zhytomyr region. Within the deposit, several areas have been identified, including Bukinska.The purpose of the publication. To investigate the ilmenite ore-bearing of the polygenic-polychronic spatial-paragenetic ore-bearing system within the Bukinska area, which is composed of ore-bearing rocks of the foundation, their weathering crust, continental alluvial (Aptian-Lower Albian) deposits (formed due to erosion and redeposition of eluvium) and coastal-sea (Turonian) formations (formed due to erosion and redeposition of Lower Cretaceous alluvium and partially weathering crust).Materials and Methodology. The methodical and methodological basis of the research was the work of the autors on the structural and lithological modeling of placers of heavy minerals. The actual material for the studies were the production reports and scientific publications. A target database was created for cartographic modeling of the structure and quality indicators (distribution of ilmenite content along the lateral spread and vertical cross-sections of wells) of the rocks. The database contains the coordinates of 1635 wells, their description, test results. Cartographic constructions were made in Inkscape, Golden Software Strater, and Golden Software Surfer software. Correlations between certain parameters of ore-bearing sediments were studied in Microsoft Excell.Main Results. Information on the geological structure of the Bukinska area of the Mezhyrichne titanium ore deposit is given. It has been found that the ore-bearing potential of the area is determined by a polygenic-polychronic spatially-paragenetically connected ore system. This ore system is composed of titanium-bearing rocks of the crystalline basement of the Volodarsk-Volyn complex, their weathering crusts, Lower Cretaceous continental, Upper Cretaceous coastal – marine products of erosion and redeposition of eluvium and to a lesser extent and partially heterogeneous formations of the Quaternary system. Maps of the relief of the bottom, the top surface and thickness of the ore-bearing rocks have been constructed. The lateral distribution of the average ilmenite content in all rock types was studied. The directionality and strength of correlations were investigated. The peculiarities of the distribution of ilmenite in the vertical section of formations of different ages and different genesis have been clarified.Conclusions. A target database was created, on the basis of which a set of maps was built, which made it possible to study the structural and material parameters of ore-bearing deposits. The ore-bearing potential of the polygenic-polychronic spatial-paragenetic system of the Bukinska area was qualitatively and quantitatively assessed. It has been found that the Bukinska area, within which there is a spatially and paragenetically combined temporal and heterogeneous ore bearing, has a significant ore-bearing potential and is attractive for investment. The obtained results are an information base for supporting mining operations.